229k views
3 votes
Which represents “if x=4, then y=-2”

User Privateace
by
5.9k points

2 Answers

3 votes
You haven't shared the answer choices.

Still, we could invent a function for which the above statement is true:

y = mx + b, and "if x = 4, y = -2" becomes -2 = m(4) + b. Unfortunately, we have 2 unknowns here.

If we arbirtrarily let b = 3, then y = mx + b becomes y = mx + 3. Subst. 4 for x and -2 for y, we get -2 = m(4) + 3, or -5 = 4m, or m = -5/4.

Then y = mx + b becomes y = (-5/4)x + 3. (this is just an example!!!)


User Irgendw Pointer
by
6.0k points
0 votes
Representa una ecuacion de segundo grado. :v
User Mmd Amin
by
5.4k points